Hubungan Penggunaan Gadget Terhadap Perubahan Perilaku Pada Remaja - Yanti, Nova Dwi; Mardison, Lydia; Dewi, Ratna; Yenni, Yenni (Universitas Fort De Kock Bukittinggi, 2021)
Gadgets are not only used for communication but also it is developed into devices that can do almost anything that supports activities in every aspect of human life. Excessive use of gadgets can put a person at risk of changing behavior. The purpose of this research was to determine The Correlation between of Gadget Toward Behavior Changes of Adolescents at SMP N 5 Bukittinggi, 2021.The type of this research was an analytic survey design with a cross sectional approach. The population was all students of class IX. They were 167 students. By using quota Sampling technique, 86 students were chosen as the samples. The data were collected through questionnaires. Then, it was analyzed by univariate analysis was performed to determine the frequency distribution and bivariate analysis with the Chi-Square correlation test. The results showed that (89.5%) respondents with the use of gadgets were at risk category, namely> 2 hours a day and (58.1%) respondents were at risk of experiencing changes in behavior. Then, the result of this research obtained that there was a significant relationship between the use of gadgets and changes in adolescent behavior with a p value = 0.031 and an OR value = 5.793. In short, it is concluded that there was a relationship between excessive use of gadgets and changes in adolescent behavior at SMP Negeri 5 Bukittinggi in 2021. Then, it is expected that the results of this research can be used as a source of information for students regarding the use of gadgets to prevent or minimize the risk of behavior change such as health, social interactions, etc. Keywords : Gadget use, Behavior Change, Adolescents.